Commercialization of Alate Termites (Macrotermes Sp.) To Improve Households' Livelihoods in Vihiga County, Kenya - Anyuor, S.; Ayiko, Monica; Amulen, D. (African Journal of Food, Agriculture, Nutrition & Development, 2022)
To meet the rising demand for animal-based protein, conventional livestock may prove expensive as the current production system remains unsustainable. This calls for intervention research on alternative sources of protein, hence a switch to affordable and environmentally acceptable protein sources of which approximately 1,900 insect species are consumed worldwide. Alate termites have thus received considerations in this line for nutritional and economic benefits. Trading of alate termites is becoming a valuable source of income for many people in Vihiga county and other parts of western region, which although modest in terms of monetary value, could nonetheless form a significant proportion of their annual income. Information about commercialization of alate termites and its impact to household level food security has remained sparse. The goal of this research was to partly fill this knowledge gap and document the associated potential of alate termite commercialization on household livelihoods in Luanda and Hamisi sub-counties of Vihiga county. A total of 204 respondents participated in the cross-sectional study. Chi Square and regression analysis was employed to predict association and relationship between alate termite collection and marketing and household income for improved livelihoods. The results affirmed that, alate termites are a delicacy and cultural food eaten by the majority of the people in western Kenya. This is attributed to its nutritional value as well as higher economic potentiality. The average retail price per kilogram of 500 Kenya Shillings (US $5), compares favorably with that of goat meat, which is retailed within the region. The trading of alate termites is dominated by women and characterized by wholesalers who buy the alates from collectors and sell to retailers. The purpose of utilization was positively significant p<0.005. Inferring that the benefits realized from utilization of alate termites was dependent on households' decisions regarding various utilization purposes. Drying was the most common preservation method (64%) whereas others have a preference for frying. Moreover, alate termites are grounded into flour that is used for baking other products. The potential of alate termites to diversify household livelihood can be fully explored in order to contribute to household livelihoods and ultimately food security.
Keywords: Alate Termites; Household Livelihoods; Marketing; Utilization; Value Addition